MODEL PEMBELAJARAN ARIAS (ASSURANCE, RELEVANCE, INTEREST RELEVANCE, SATISFACTION) DALAM MATERI IPA BAGI SISWA TUNARUNGU SMPLB - TRY WAHYU N, RECHA (Jurnal Pendidikan Khusus, 2017)
Abstract Learning model of ARIAS (Assurance, Relevance, Interest, Assesment, Satisfaction) As a lesson that instills confidence student, relevance with a children life and happily. This research had purpose (1) to state the readiness done by the teacher in the implementation of learning model of ARIAS in science for deaf student in SMPLB Karya Mulia Surabaya. (2) To describe the learning prosses in learning model of ARIAS in science by teacher and deaf students response, and (3) to describe the obstacles experienced in applying ARIAS learning model and solution will be given. The research used descriptive method of qualitative approach. research subyect is a teacher and deaf student in class VIII of SMPLB Karya Mulia Surabaya. The technique of data collection by observation, documentation and interview, data analysis used the steps of reduction data, display data, and verification / concluding. The results of the research are (1) the readiness done by the teachers in learning model of ARIAS in science lessons to deafstudent in SMPLB Karya Mulia Surabaya was arranging the modified syllabus and RPP, teaching materials adapted to the students ability, prepairing of learning media, and making assessment sheets. (2) The learning procces in learning model of ARIAS by the teacher in science lesson to deaf student could be applied well with percentage of implementation above 80%. ARIAS learning model gets good response from students, students are more active in learning and student evaluation result shows good learning progress. (3) The obstacles is the condition of interest in learning some deaf students are volatile change. The solution is to do variations of learning activities, doing ice breaking or giving more motivation by teachers and other students. The ARIAS learning model is more readily accepted by students with high abilities than students with less ability. the solution is to give more attention to the student with less ability and give understanding to all students to be able to work together.     Keywords : Learning model of ARIAS (Assurance, Relevance, Interest, Assesment, Satisfaction), science.